Enterprise risk management in healthcare organizations - SAJWANI, REHAB (2021)
Background & Purpose – Risk management is changing dramatically as organizations move away from old, siloed approaches and toward an enterprise-wide strategy. Organizational Risk Management (ERM) emerged as a new approach for managing organizational risks, concentrating on mechanisms to increase corporate governance and risk management in a holistic manner across many enterprise domains. The aim of this research is to explore the different factors that contribute to the success of ERM in healthcare organizations. For doing this the author examines global scenarios of implementation of ERM in healthcare organizations as well as its further insights during Covid-19. Main findings from the literature indicating that there is a fundamental gap on the implementation of ERM in the UAE healthcare sector. Design/methodology/approach– The study examines the organizational factors that led to effective ERM. A quantitative methodology using survey questionnaire was conducted online for 100 employees in Tashafi al-Futtaim clinics. To give a better representation of Tashafi healthcare group, the sampling frame was based on random sampling of board of directors, senior and Junior Management. The respondents were asked questions about the organizational factors that contributed to the implementation of effective ERM in the organization including the governance and culture in their organization; Strategy development plans; ongoing Risk assessment; Information and communication; Roles and responsibilities of risk management team and Monitoring and control within the organization. Findings – Based on gathered data using SPSS, the study is statistically significant, additionally the six organizational factors in the study have positive correlation to implementation of effective ERM. However, different levels of agreement of each independent variable to dependent variable indicate different levels of contribution of each organizational factor on effective implementation of ERM. Findings present that the study organization has high agreement and correlation on contribution of governance and culture, and Monitoring and control to the effective implementation of ERM. While strategy development, risk assessment, Roles and responsibilities, and information and communication had mixed agreement to effective implementation to ERM. Research limitations/implications – The survey was conducted on Tashafi AL Futtaim clinics management employees through online link on google forms this presented a limitation of diverse sample of employees conducting the survey. Furthermore, the study is limited to a single healthcare institution, limiting the impact of organizational factors on effective ERM implementation. Practical Implications-. Despite these advancements, little research has been done on the elements that contribute to effective ERM adoption. The demand for ERM adoption has prompted organizations in a variety of industries, including healthcare, to adopt it as it is necessary to address risk management in healthcare to be within context of patient safety. Originality/value – Although large number of articles and studies have explored enterprise risk management (ERM), there are little data about effective ERM implementation in healthcare organizations in the Middle East specifically in Dubai. Keywords: Risk management, Enterprise risk management, healthcare organization, organizational factors, governance and culture, strategy development, risk assessment, monitoring and control, roles and responsibilities, information, and communication